Evaluation of Mathisen's technique for ureteral reimplantation in children with primary vesicoureteral reflux. Issue 6 (December 2016) - Haid, Bernhard; Strasser, Christa; Becker, Tanja; Koen, Mark; Berger, Christoph; Roesch, Judith; Stuehmeier, Jannik; Schlenck, Barbara; Horninger, Wolfgang; Oswald, Josef
Summary: Introduction: Although cross-trigonal ureteral reimplantation (Cohen) is a commonly used technique in children, it represents a non-physiological transfer of the ureteral orifices and may prove challenging with regard to endoscopic ureteral operations in later life. In 1964, Mathisen described an alternative method of ureteral reimplantation with lateralization of the neohiatus, creating an orthotopic course of the submucosal ureter. We have evaluated success and complication rates of both techniques that were applied sequentially at our departments. Methods: Forty-eight consecutive patients (83 ureters, 24 males/24 females) following Mathisen reimplantation were compared with 53 consecutive patients (98 ureters, 30 males/23 females) following Cohen reimplantation. Inclusion criteria were primary vesicoureteral reflux (VUR) and no previous intervention. Reflux grades (Mathisen 58 ureters/69.9% VUR ≥ III; Cohen 66 ureters/66.7% VUR ≥ III) and the occurence of other complicating factors (ureteroceles, megaureters, posterior urethral valves) in both groups were comparable. Results: After Cohen's reimplantation there were no immediate complications requiring intervention; during follow-up (mean 28.2 months) three patients (5.6%) suffered febrile urinary tract infections (UTIs), of which one (1.8%) was diagnosed with a persisting VUR. Persistent hydronephroses (≥II SFU) were recorded in six patients (13.2%). After reimplantation using Mathisen's technique, two patients (4.1%) suffered significant intravesical bleeding; during follow-up (mean 23.06 months) four patients (8.3%) suffered febrile UTIs, and seven patients (14.5%) were diagnosed with persisting VUR after a mean follow-up of 10.8 months. The patients with persistent VUR had more commonly high-grade (IV and V) VUR initially, compared to the whole group. Two patients (4.1%) had persistent hydronephroses (≥II SFU). Mathisen's technique for ureteral reimplantation yielded a significantly ( p  = 0.0256 patients, p  = 0.006 ureterorenal units) lower success rate (85.5% patients, 89.2% ureterorenal units) in comparison with Cohen's technique (98.2% patients, 99% ureterorenal units). Although there was no intervention for obstruction, persistent hydronephrosis was more common in the Cohen group (13.2% vs. 4.1%, n.s.). Conclusions: Despite the advantages of an orthotopic ureteral orifice close to the bladder neck, as achieved by Mathisen's reimplantation, cross-trigonal ureteral reimplantation proved more reliable for VUR correction. As regards optimizing the results, patient selection for either technique could prove essential. Nevertheless, as regards the difficulties with ectopic ureteral orifices in the Cohen technique in the long-term follow-up, the concept of anatomic, orthotopic ureteral reimplantation should be pursued and the technique should be further refined. Figure Persistent VUR (patients) after Mathisen (7/48 patients, 14.5%) and Cohen (1/53 patients, 1.8%) reimplantation.